Effect of environmental factors on seminal microbiome and impact on sperm quality - Neto, Filipe T. Lira; Viana, Marina C.; Cariati, Federica; Conforti, Alessandro; Alviggi, Carlo; Esteves, Sandro C. (Frontiers in Endocrinology, 2024)
Objective: This review provides a comprehensive overview of the existing research on the seminal microbiome and its association with male infertility, while also highlighting areas that warrant further investigation.: A narrative review was conducted, encompassing all relevant studies published between 1980-2023 on the male reproductive tract microbiome in humans. This review considered studies utilizing culture-based, polymerase chain reaction (PCR)-based, and next-generation sequencing (NGS)-based methodologies to analyze the microbiome. Data extraction encompassed sample types (semen or testicular tissue), study designs, participant characteristics, employed techniques, and critical findings.We included 37 studies comprising 9,310 participants. Among these, 16 studies used culture-based methods, 16 utilized NGS, and five employed a combination of methods for microorganism identification. Notably, none of the studies assessed fungi or viruses. All NGS-based studies identified the presence of bacteria in all semen samples. Two notable characteristics of the seminal microbiome were observed: substantial variability in species composition among individuals and the formation of microbial communities with a dominant species. Studies examining the testicular microbiome revealed that the testicular compartment is not sterile. Interestingly, sexually active couples shared 56% of predominant genera, and among couples with positive cultures in both partners, 61% of them shared at least one genital pathogen. In couples with infertility of known causes, there was an overlap in bacterial composition between the seminal and vaginal microbiomes, featuring an increased prevalence of Staphylococcus and Streptococcus genera. Furthermore, the seminal microbiome had discernible effects on reproductive outcomes. However, bacteria in IVF culture media did not seem to impact pregnancy rates.Existing literature underscores that various genera of bacteria colonize the male reproductive tract. These organisms do not exist independently; instead, they play a pivotal role in regulating functions and maintaining hemostasis. Future research should prioritize longitudinal and prospective studies and investigations into the influence of infertility causes and commonly prescribed medication to enhance our understanding of the seminal microbiota's role in reproductive health.